Composite leading indicators for Ukraine: An early warning model - Janusz Szyrmer; Vladimir Dubrovskiy; Inna Golodniuk (Center for Social and Economic Research (CASE), 2009)
Our objective has been to experiment with diverse economic indicators in order to help equip Ukrainian policymakers with a relatively simple tool, which could deliver warning signals about a possibility of upcoming economic problems and thereby assist the Government in designing policy instruments which would help prevent or soften a slowdown or recession. The project has undertaken the following tasks: Based on an analysis of the pattern of growth of the Ukrainian economy since the end of the post-Soviet recession (the year 2000) we have formulated the hypotheses concerning the factors preceding/affecting the upturns and downturns (with a focus on the latter) of the country's growth; We have studied international “best practice” in early warning indicators in order to design a similar system for Ukraine; We have selected the relevant indicators, consistent with our hypotheses and used a probit model in order to experiment with these indicators; The final set of indicators used in the model included the following lagged independent variables: changes in the value of export, changes in real Exchange rate of the hryvnya, producers' price index adjusted for domestic price inflation index and the IMF's metal price index, bank credit interest rate, changes in the industrial output of the European Union; our dependent variable (which was used as a proxy for the overall economic growth) was changes in real industrial output; The model was used to formulate a warning forecast for the Ukrainian economy for the second half of 2008 based on the data for the January 2000 - June 2008 period; all predictions for the second half of 2008 have delivered warning about a downturn of the Ukrainian economy; We ran a few additional experiments with the model, and We have recommended several further steps of analysis toward a full implementation and institutionalization of such a model in the near future.
Keywords: E32; E37; C53; 330; business cycle; forecasting; econometric model; Ukraine; Ukrainian economy; economic growth; GDP; early warning indicator; Konjunktur; Frühwarnsystem; Konjunkturindikator; Ukraine